Dār al-Ḥarb as the Motherland? The Muslim Tatars of (the Grand Duchy of) Lithuania and Social Contract. (29th November 2016) - Račius, Egdūnas
Abstract : Muslim presence in Lithuania, though already addressed from many angles, has not hitherto been approached from either the perspective of the social contract theories or of the compliance with Muslim jurisprudence. The author argues that through choice of non-Muslim Grand Duchy of Lithuania as their adopted Motherland, Muslim Tatars effectively entered into a unique (yet, from the point of Hanafi fiqh, arguably Islamically valid) social contract with the non-Muslim state and society. The article follows the development of this social contract since its inception in the fourteenth century all the way into the nation-state of Lithuania that emerged in the beginning of the twentieth century and continues until the present. The epitome of the social contract under investigation is the official granting in 1995 to Muslim Tatars of a status of one of the nine traditional faiths in Lithuania with all the ensuing political, legal and social consequences for both the Muslim minority and the state.